A Survey on Privacy Concerns in Blockchain Applications and Current Blockchain Solutions to Preserve Data Privacy - Baskaran H.; Yussof S.; Rahim F.A. (Springer, 2023)
Access control; Blockchain; Health care; Internet of things; Access control policies; Access control protocol; Cryptographic protocols; Decentralization; Health care application; Immutable; Internet of Things (IOT); Secure multi-party computation; Data privacy